2013
DOI: 10.1007/s00227-013-2282-9
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of ocean acidification research

Abstract: This special issue compiles 37 manuscripts investigating the biological impacts and societal relevance of ocean acidification. It includes important considerations regarding experimental design, new methods and how ocean acidification science can contribute to society through education and socioeconomic assessment. Altogether, this special issue constitutes a snapshot of recent ocean acidification research. This paper aims at summarizing the key findings and highlights future challenges and research priorities. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 42 publications
(60 reference statements)
2
39
0
Order By: Relevance
“…As a result of human activity, the atmospheric CO 2 concentrations increased from 280 ppmv in 1750 (pre-industrials atmospheric CO 2 levels) to over 391 ppmv in 2011 (IPCC, 2013), corresponding to a reduction of 0.1 units in the oceans pH (Caldeira and Wickett, 2003;IPCC, 2013), and it is expected that pH will further decrease from 0.06 to more than 0.3 units within the end of the 21st century (IPCC, 2013). Several studies revealed that the pH decrease, associated with changes in seawater chemistry, seem to have negative effects on marine ecosystems, namely on bivalves, crustaceans and fish survival capacity, physiology, growth, reproductive capacity, behaviour and development (among others, Campbell et al, 2014;Doney et al, 2012;Dupont and P€ ortner, 2013;Garrard et al, 2013;Lane et al, 2013;Langenbuch and P€ ortner, 2003;Langenbuch et al, 2006;Michaelidis et al, 2005;Widdicombe and Spicer, 2008;Wickens, 1984). Additionally, reproductive capacity may also be affected by water acidification (Widdicombe and Spicer, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…As a result of human activity, the atmospheric CO 2 concentrations increased from 280 ppmv in 1750 (pre-industrials atmospheric CO 2 levels) to over 391 ppmv in 2011 (IPCC, 2013), corresponding to a reduction of 0.1 units in the oceans pH (Caldeira and Wickett, 2003;IPCC, 2013), and it is expected that pH will further decrease from 0.06 to more than 0.3 units within the end of the 21st century (IPCC, 2013). Several studies revealed that the pH decrease, associated with changes in seawater chemistry, seem to have negative effects on marine ecosystems, namely on bivalves, crustaceans and fish survival capacity, physiology, growth, reproductive capacity, behaviour and development (among others, Campbell et al, 2014;Doney et al, 2012;Dupont and P€ ortner, 2013;Garrard et al, 2013;Lane et al, 2013;Langenbuch and P€ ortner, 2003;Langenbuch et al, 2006;Michaelidis et al, 2005;Widdicombe and Spicer, 2008;Wickens, 1984). Additionally, reproductive capacity may also be affected by water acidification (Widdicombe and Spicer, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…While sponge diversity was found to increase at low pH sites (pH 7.8–7.9) in the Mediterranean (Goodwin et al ., ), sponge diversity decreased at low pH sites (pH 7.73–8.00) in Papua New Guinea (Fabricius et al ., ), although particular species did become significantly more abundant at sites with active CO 2 bubbling (Morrow et al ., ). Although these studies provide some insight into sponge responses to a changing climate, the co‐occurrence of OW and OA requires studies that consider these factors concurrently (Dupont & Pörtner, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is the combination of information collected in laboratory experiments, field observations (monitoring), CO 2 vents, laboratory mesocosms, FOCE, and modeling that will allow for the required mechanistic understanding and predictive power to be provided (Dupont and Pörtner, 2013).…”
Section: Discussionmentioning
confidence: 99%